Sifat mekanik dan morfologi termoplastik elastomer (TPE) hasil polipaduan NBR/PVC dan maleat anhidrat - Arum Yuniari (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2012)
ABSTRACTThe research of thermoplastic elastomer NBR/ PVC and maleic anhydride (MAH) aimsto determine the effect of maleic anhydride (MAH) as compatiblizer on the mechanicalproperties and morphology of thermoplastic elastomer NBR / PVC. Mixing between the NBRand PVC performed using a two roll mill with a temperature range of 60-80 º C, the vulcanizationprocess using a hydraulic press at a temperature of 170 º C, pressure of 150 kg/cm2. Compositionof the NBR / PVC successively varied: 90/10: 85/15 /: 80/20: 75/25: 70/30 and 65/35, being theamount of maleic anhydride (MAH) as compatibilizer used are 4 and 5 phr. Mechanicalproperties were evaluated including tensile strength, elongation at break, hardness andcompression set according to ASTM procedure.Thermal treatments were performed by means ofthermogravimetry (TG) and morphology of the blend by scanning electron mycroscopy (SEM).Test results showed that MAH compatibilizer be able to improve the mechanical properties oftensile strength and elongation, and compresion set. Morphological observation by SEM showedthat the addition of MAH causes more homogeneous mixture. Thermal analysis by TG appearsthat the melting temperature of the mixture was 252 º C.Keywords: thermoplastic elastomer, NBR, PVC, maleat anhydride.ABSTRAKPenelitian termoplastik elastomer polipaduan NBR/PVC dan maleat anhidrat (MAH)bertujuan mengetahui pengaruh kompatibliser maleat anhidrat (MAH) terhadap sifat mekanikdan morfologi termoplastik elastomer NBR/PVC. Pencampuran antara NBR dan PVC dilakukanmenggunakan two roll mill dengan rentang suhu 60 80 ºC, proses vulkanisasi menggunakanhydraulic press pada suhu 170 ºC, tekanan 150 kg/cm2. Komposisi NBR/PVC divariasi berturutturut:90/10; 85/15/; 80/20; 75/25; 70/30 dan 65/35. Jumlah kompatibiliser maleat anhidrat(MAH) yang digunakan adalah 4 dan 5 phr. Pengujian sifat mekanik meliputi tegangan putusdan perpanjangan putus, kekerasan dan compression set menggunakan metode ASTM.Morfologi termoplastik vulkanisat diuji menggunakan SEM dan DTA. Hasil pengujianmenunjukkan bahwa kompatibiliser MAH mampu meningkatkan sifat mekanik tegangan putusdan elongation dan compresion set. Pengamatan morfologi dengan SEM menunjukkan bahwapenambahan MAH menyebabkan campuran lebih homogen. Analisis termal dengan TG tampakbahwa suhu leleh campuran adalah 252 ºC.Kata kunci: termoplastik elastomer, NBR, PVC, maleat anhidrat.